Práticas de escrita em um contexto de formação continuada: um estudo etnográfico do curso de especialização linguagem e tecnologia - Raquel Aparecida Soares Reis Franco (2015)
Over the past decades, there has been a significant increase in research dealing with writing practices in Basic Education. However, little has been investigated in the Brazilian context in the field of academic literacies (MARINHO, 2010a; OLIVEIRA, 2011; PASQUOTTE-VIEIRA, 2014). Considering this context, this study aimed to analyze and understand the meanings of writing practices in the post-graduation course Language and Technology, LINTEC, offered by an institution of higher education in the metropolitan area of Belo Horizonte, Minas Gerais. I consider the assumptions of the New Literacy Studies (NLS) group (LILLIS; SCOTT, 2007; LEA; STREET, 1998), since this group conceives literacy as a social practice. Using the principles of the ethnographic perspective (HEATH, 1982; STREET, 2003 CASTANHEIRA, 2004; GREEN; DIXON; ZAHARLIC, 2002), I followed for one year and a half the course LINTEC, adopting these following methodological procedures: video recordings, field notes, participant observation, analysis of the institutional space and interviews with students and teachers of the course. From a holistic perspective, first of all, presented the organization of classes and writing practices that have occurred in face to face classroom and in the online classroom. I sought to draw the intertextual nature of how students were engaged in the written production in the research group. Then I selected two significant cases (MITCHELL, 1984) which were described, analyzed and interpreted (Wolcott, 1994). The result of the study showed that the meanings of writing, for the participants, constitute what Street (1984) calls the autonomous model of literacy. It also highlighted the tense and confrontational nature of the interactions mediated by writing in the post-graduation course. Beyond that, I demonstrated the need to reflect, taking as a reference the ideological model of literacy (STREET, 1984) about that literacy concepts that guide the continuing education courses.